1989
DOI: 10.1007/bf00931811
|View full text |Cite
|
Sign up to set email alerts
|

Lectin-binding sites in the midgut of the mosquitoesAnopheles stephensi Liston andAedes aegypti L. (Diptera: Culicidae)

Abstract: The presence and distribution of binding sites for eight different lectins, Con A, DBA, HPL, LFA, RCA I, SBA, UEA I, and WGA, were compared in the midguts of Plasmodium gallinaceum-infected Aedes aegypti and Plasmodium berghei-infected Anopheles stephensi. Lectins with high specificity for N-acetyl-D-glucosamine (GlcNAc) exhibited high binding preference for the peritrophic membrane and microvillar glycocalyx of Ae. aegypti; the same structures were preferentially labeled by N-Acetyl-D-galactosamine (GalNAc)-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 24 publications
2
46
0
Order By: Relevance
“…As the parasite was seen in ultrastructural studies to disrupt the membrane (3), the biochemical basis of penetration would depend on the chemical composition of the membrane. The peritrophic membrane had been suggested, from indirect studies, to consist of chitin (9). The demonstration in the present study of the release of N-acetylglucosamine by the action of chitinase provides direct evidence for the presence of chitin in A. agypti peritrophic membrane.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…As the parasite was seen in ultrastructural studies to disrupt the membrane (3), the biochemical basis of penetration would depend on the chemical composition of the membrane. The peritrophic membrane had been suggested, from indirect studies, to consist of chitin (9). The demonstration in the present study of the release of N-acetylglucosamine by the action of chitinase provides direct evidence for the presence of chitin in A. agypti peritrophic membrane.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies demonstrated that lectins specific for N-acetylglucosamine bind to the peritrophic membrane and proposed that the membrane contains chitin [Rudin, W. & Hecker, H. (1989) Parasitol. Res.…”
mentioning
confidence: 99%
“…Consequently, the arthropod midgut serves as both barrier and gateway to pathogen invasion (97,107). The luminal face of the midgut epithelium is covered by a dense array of glycoconjugates that may act as a "glycan receptor-buffet" for a myriad of pathogens (107).…”
Section: The Midgut: the Principal Pathogen Gatewaymentioning
confidence: 99%
“…Another protective structure is the glycocalyx (glyco ϭ sweet͞sugar, calyx ϭ shell), which is an integral part of the microvillar membrane and appears as an electron-dense fuzzy coat on the outside of the microvillar surface (4,10). The glycocalyx, including that of mosquitoes, is rich in carbohydrates, as it is recognized by a variety of lectins (11,12). However, no experimental data are currently available on the molecular composition of the insect midgut glycocalyx.…”
mentioning
confidence: 99%